STUDY OF SECONDARY SCHOOL SOCIAL STUDIES TEACHER UNDERSTANDING ABOUT GEOGRAPHY LITERATION - Sugiyanto, Sugiyanto (Universitas Pendidikan Indonesia, 2017)
This study aims to: (1) know the teacher's understanding about the concept of Geography as a platform in Social Studies learning; (2) know the teacher's understanding about geography literacy as a platform in Social Studies learning; and (3) study the right literacy concept as platform for Social Studies lesson. This research uses survey method. The subjects of the study were Social Studies teachers in Surakarta City. Sampling using startified random sampling. The results showed: 1) 76% of respondents do not understand about Geography as a platform in Social Studies learning; 2) 80% of respondents have not understood geography literacy; 3) Edelson's geography literature which consist of interaction, interconnection, and implication components can be used as an alternative to the implementation of Geography policy as a Platform in Social Studies.